Stimulan® Antibiotic Impregnated Beads for the Treatment of Diabetic Foot Infection - Hazel Ting Wai Chon; Maher Hamish; Piranavan Kirupananthan; Aimen Gmati; Hiba Abdalla; Robert Hicks (The Arab Journal of Interventional Radiology, 2020)
Context: Limited evidence has been found on the effectiveness of Stimulan® antibiotic beads for the treatment of diabetic foot ulcer. Aims: The aim of the study was to evaluate the safety and efficacy of Stimulan® antibiotic beads in treating diabetic foot infection and review the healing rate, infection recurrence rate, and the length of postoperative hospital stay. Settings and Design: It was a retrospective review of patients implanted with Stimulan® antibiotic beads at a district general hospital in England from 2017 to 2019. Subjects and Methods: Nineteen patients with Wagner Grade 3 and 4 ulcers were included, with a mean age of 62.3 years. Stimulan®, an antibiotic loaded absorbable calcium sulfate biocomposite, was used to treat persistent diabetic foot infection with chronic osteomyelitis. Staphylococcus aureus was the most common bacteria isolated. Exclusion criteria consisted of those with Wagner Grade 1 or 2 ulcers and infections that had clinically responded to long courses of systemic antibiotics treatment. Results: All patients underwent local wound debridement with the application of Stimulan® beads and received intravenous antibiotics for 48 h postoperatively. The average postoperative hospital stay was 2 days. After 1 month of follow-up, 16 wounds (84%) fully healed, two wounds (11%) had partially healed, and one wound (5%) showed no sign of healing. Two patients (11%) had shown recurrence of diabetic foot infection in a different foot after 24 months. Amputation rate was 0% over 24 months. Conclusions: This study recorded the clinical efficacy of Stimulan® antibiotic beads by demonstrating 0% amputation rate after two years and shortened hospital stay. With a low recurrence rate (16%), Stimulan® beads could be considered as one of the alternative treatments in managing diabetic foot infection.